Family Members' and Intensive Care Unit Nurses' Response to the ECG Memento© During the Bereavement Period. Issue 6 (November 2017) - Beiermann, Mary; Kalowes, Peggy; Dyo, Melissa; Mondor, Amanda
Abstract : Background: In the United States, 20% of patients die in the intensive care unit (ICU), yet little is known about bereavement strategies to aid grieving families. Objective: The primary aim was to study the bereavement experience for families in the ICU; secondary aim was to measure nurses' perception of end-of-life care, and a third was to evaluate the impact of the ECG Memento © by families and nurses. Methods: A prospective, descriptive study design was used, with a postsurvey methodology. Fifty ICU patient families agreed to participate, although only 28 returned the Satisfaction With Bereavement Experience Questionnaire. In addition, 38 of 100 eligible nurses completed the Quality of Dying and Death in the Intensive Care Unit survey. Results: The Satisfaction With Bereavement Experience Questionnaire data showed families as highly satisfied with hospital (mean, 1.5), personal (mean, 1.6), ritual (mean, 1.3), and posthospital experiences (mean, 1.9). Quality of Dying and Death in the Intensive Care Unit results indicated that ideal control of patients' symptoms was reported by only 26% of nurses surveyed. Half of the families reported that the death was unexpected. Families (86%) responded positively to the ECG Memento ©, and according to 98% of the nurses, the ECG Memento © was very well received. Discussion: Despite most families reporting high satisfaction with the bereavement experience, nurses reported a low level of patient symptom control; also, families often found the death to be unexpected. This suggests that the bereavement experience is a complex process requiring nurses to implement various interventions during this vulnerable period. Most families responded positively to this novel bereavement tool, which may aid families as they transition from anticipatory grieving to bereaved status. Further studies are needed to evaluate the ECG Memento © as an innovation on a wider scale and to develop additional interventions to positively impact the grieving process for families.